2010
DOI: 10.17816/edgcc1166-76
|View full text |Cite
|
Sign up to set email alerts
|

Methane emission from middle taiga ridges and ryams of Western Siberia

Abstract: В статье приводятся экспериментальные данные по потокам метана с рямов и гряд средней тайги Западной Сибири. Эти данные объединяются в рамках «стандартной модели» Bc7, включающей в себя медианы распределений потоков метана с шести типов микроландшафтов, их площади в ячейках географической сетки 0.5°×0.5° и продолжительность периода эмиссии метана для данной зоны. На основании модели Вс7 годовая эмиссия СН4 из средней тайги Западной Сибири оценена величиной 0.69 МтСН4/год, что составляет 21.6% региональной эмис… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
2
0
1
Order By: Relevance
“…In contrast, the water-table level varied from 10.5 to 4 cm below the hollow surface at RH and from 3 cm below the surface to 1 cm above the surface at WH, thereby preventing methane oxidation and methanotrophic activity. These results support previous conclusions based on observations at Siberian peatlands and at Mukhrino [23,24]. It should be noted that the median values of CH 4 flux from the hollow and the waterlogged hollow (6 and 11 mgCH4 m −2 h −1 , respectively) fall well within the range of methane emissions from hollows reported for Mukhrino earlier [24], although slightly exceed the median values.…”
Section: Ch 4 Emissionssupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, the water-table level varied from 10.5 to 4 cm below the hollow surface at RH and from 3 cm below the surface to 1 cm above the surface at WH, thereby preventing methane oxidation and methanotrophic activity. These results support previous conclusions based on observations at Siberian peatlands and at Mukhrino [23,24]. It should be noted that the median values of CH 4 flux from the hollow and the waterlogged hollow (6 and 11 mgCH4 m −2 h −1 , respectively) fall well within the range of methane emissions from hollows reported for Mukhrino earlier [24], although slightly exceed the median values.…”
Section: Ch 4 Emissionssupporting
confidence: 91%
“…Mukhrino represents a typical landscape of an oligotrophic raised boreal peatland [4]. Earlier studies addressed both CO 2 [20][21][22] and CH 4 [23][24][25] fluxes at Mukhrino and stressed differences across the microlandscapes. Namely, it was found that the net exosystem exchange of CO 2 averaged over three growing seasons at the hollow site was significantly higher than at the ridge site.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies were performed in the Mukhrinskaya River Valley (60°53=N, 68°42=E), Khanty-Mansi Autonomous Okrug, West Siberia, Russia, where the mean annual temperature is Ϫ1.1°C and the mean annual precipitation is 596 mm. Other characteristics of the study site have been described previously (25)(26)(27). This is one of the poorly accessible and virtually unpopulated taiga regions.…”
Section: Methodsmentioning
confidence: 99%
“…1;Ambus, Robertson, 2006, Fig. 3;Kleptsova et al, 2010;Glagolev et al, 2012]), в связи с чем полученную погрешность имитации можно признать вполне удовлетворительной.…”
Section: заключениеunclassified